Circulating CD56dim natural killer cells and CD56+ T cells that produce interferon‐γ or interleukin‐10 are expanded in asymptomatic, E antigen‐negative patients with persistent hepatitis B virus infection. Issue 3 (3rd September 2014) - Conroy, M. J.; Mac Nicholas, R.; Grealy, R.; Taylor, M.; Otegbayo, J. A.; O'Dea, S.; Mulcahy, F.; Ryan, T.; Norris, S.; Doherty, D. G.
Summary Infection with hepatitis B virus (HBV) can result in spontaneous resolution or chronic infection, which can remain asymptomatic or can progress to cirrhosis and/or hepatocellular carcinoma. The host immune response is thought to be a major determinant of the outcome of HBV infection and virus‐specific cytotoxic T lymphocytes (CTL) can mediate immunity against the virus and cause liver pathology. Antigen‐nonspecific innate lymphocytes may also contribute to HBV infection and liver disease, therefore, we examined the frequencies, phenotypes, cytolytic activities and cytokine profiles of circulating natural killer (NK) cells, CD1d‐restricted invariant natural killer T (iNKT) cells and CD56+ T cells in 102 asymptomatic HBV‐infected patients and compared them with those in 66 uninfected control subjects. NK cells expressing low levels of CD56 (CD56dim) and CD56+ T cells were significantly expanded in the circulation of HBV‐infected patients compared with control subjects. CD1d expression and iNKT cell frequencies were similar in both groups. Despite these expansions, we did not detect augmented natural or cytokine‐induced cytotoxicity in the HBV‐infected subjects. All lymphocyte populations studied produced interferon‐γ (IFN‐γ) significantly more frequently when taken from HBV‐infected patients compared with when taken from healthy controls. Additionally, NK cells from the patients more frequently produced interleukin‐10. As our HBV‐infected cohort consisted of asymptomatic patients with low viral loads, we propose that CD56dim NK cells and CD56+ T cells control HBV infection by noncytolytic mechanisms.